Nematode Identification and Expert System Technology 1988
DOI: 10.1007/978-1-4684-9016-9_27
|View full text |Cite
|
Sign up to set email alerts
|

Report of the Panel on Insect-Parasitic, Free-Living Terrestrial, and Free-Living Aquatic Nematodes

Abstract: The Nemisys Protect is of interest to marine nematode taxonomists because it is likely to be a valuable teaching aid and may possibly help attract graduate students to study marine nematology.Rowever, at the present time, development of the plant-parasitic part of the protect is more important than inclusion of the marine nematodes.Likewise, the animalparasitic nematodes could be included in the project after it has been developed for the plant and soil nematodes.The most likely schedule for the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In this study, we showed that the basmati rice cultivar PB1121 is equally vulnerable to M. graminicola and M. incognita. In African countries including Kenya, Egypt, Nigeria and Ivory Coast, M. incognita caused serious damage to rice in upland cultivation systems (Babatola, 1980;Diomandé, 1984;Fortuner & Merny, 1979;Namu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we showed that the basmati rice cultivar PB1121 is equally vulnerable to M. graminicola and M. incognita. In African countries including Kenya, Egypt, Nigeria and Ivory Coast, M. incognita caused serious damage to rice in upland cultivation systems (Babatola, 1980;Diomandé, 1984;Fortuner & Merny, 1979;Namu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, investigation into the damaging potential of another root-knot nematode, M. incognita, in rice is as yet an underexplored area. A few isolated studies reported the significant damage of M. incognita to upland rice in different African countries, including Kenya, Egypt, Nigeria and Ivory Coast (Babatola, 1980;Diomandé, 1984;Fortuner & Merny, 1979;Namu et al, 2019). Using histopathological analysis, Nguyễn et al (2014) showed that rice can serve as an excellent susceptible host for M. incognita infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Prasad and his co-workers (2008b) hypothesized that switching to SRI might result in a gradual decline in populations of rice root nematode species, which prefer irrigated systems, and an increase in populations of more pathogenic species such as root knot and lesion nematodes, which prefer upland and aerobic environments. Fortuner and Merny (1979) reported that M. graminicola is found in irrigated paddy fields, but this relationship is doubtful as this nematode is known to be very susceptible to flooding, and is most probably associated with plants growing when the field is free of water as in upland rice. M. graminicola is well adapted to irrigated conditions and shallow flooding does not affect its reproduction (Prot and Matias, 1995).…”
Section: Seasonal Fluctuation Of Saprozoic Nematode Population Betwee...mentioning
confidence: 99%
“…They may survive for several weeks in roots (Ichinohe, 1988) or in soil (Bridge et al, 2005). Survival in roots is better than in soil except when the soil is dry (Fortuner and Merny, 1979). Weeds are also important as alternative hosts (Bridge et al, 2005).…”
Section: Identity and Taxonomymentioning
confidence: 99%